A participatory approach for landrace evaluation - Bioversity International (Bioversity International, 2015)
A set of factsheets about our Seeds for Needs Initiative in Ethiopia. Bioversity International's 'Seeds for Needs' initiative works with farmers to research how agricultural biodiversity can help minimize the risks associated with climate change. The concept is simple – if farmers have better information and access to a wide range of varieties, they are more able to choose what best suits their conditions and cope with unpredictable weather. Seeds for Needs is trying to encourage this by exposing farmers to more crop varieties and increase their first-hand knowledge about different traits and options available and strengthening their seed systems and seed-saving capacity so that they always have access to planting material that fits their changing needs.